Comparing Plan Recognition Algorithms Through Standard Plan Libraries - Mirsky, Reuth; Galun, Ran; Gal, Kobi; Kaminka, Gal (Frontiers in Artificial Intelligence, 2022)
Plan recognition deals with reasoning about the goals and execution process of an actor, given observations of its actions. It is one of the fundamental problems of AI, applicable to many domains, from user interfaces to cyber-security. We focus on a specific class of algorithms within plan recognition that use plan libraries as input to the recognition process. Despite the prevalence of these approaches, they lack a standard representation, and have not been compared using a common testbed. This paper directly addresses this gap by providing a standard plan library representation and evaluation criteria to consider when comparing plan recognition algorithms. This representation is comprehensive enough to describe a variety of known plan recognition problems and can be easily used by existing algorithms. We use this common representation to thoroughly compare two known approaches, represented by two algorithms, SBR and PHATT. We provide meaningful insights about the differences and abilities of these algorithms, and evaluate these insights both theoretically and empirically. We show a tradeoff between expressiveness and efficiency: SBR is usually superior to PHATT in terms of computation time and space, but at the expense of functionality and representational compactness. We also show how different properties of the plan library affect the complexity of the recognition process, regardless of the concrete algorithm used. Lastly, we show how these insights can be used to form a new algorithm that outperforms existing approaches both in terms of expressiveness and efficiency.